A Case Study of Malayan Tapir (Tapirus indicus) Husbandry Practice Across 10 Zoological Collections. Issue 3 (18th May 2012) - Rose, Paul E.; Roffe, Sarah M.
<x xml:space="preserve">Abstract</x> The Malayan, or Asian, tapir (Tapirus indicus) has a diminishing wild population and is becoming more common in captivity as zoos attempt to manage sustainable ex situ populations. Tapirs can be relatively easy to maintain and breed, but captive animals appear to suffer from reduced activity budgets, obesity, and poor public image. A questionnaire‐based survey was designed and sent specifically to 10 collections around the world that exhibit Malayan tapirs, with the aim of assessing husbandry regimes to determine prevalence of standardized practices as well as highlighting any key differences, and to showcase good practice, thus providing information beneficial to those maintaining this species in their zoo. Twenty‐five animals were included in the survey from collections across four continents. The research's major conclusions show differing dietary make‐up, with a lack of forage provision, contrasting with a diverse array of enrichment protocols used. Significant differences were noted between zoos for total amount of food offered (P = 0.000) as well as ratios of forage to concentrate pellet offered (P = 0.004). Comparing food offered to male and female tapirs with published requirements for an "average" of either gender shows not all zoos providing the amount suggested in husbandry guidelines. Intelligently designed and original enrichment was provided to all animals but differences between zoos were noted in the application and "usefulness" of enrichment for individual tapir. Overall, animals are benefiting from enrichment but welfare could be further improved via consistent feeding of ad libitum forage and regular use of browse as a constituent part of daily rations. Zoo Biol. 32:347–356, 2013. © 2012 Wiley Periodicals, Inc.